Shaping Value Orientations Through The Fusion Of Technology And Pedagogical Action Research - Antoci, Diana (Didactica Danubiensis, 2025)
Abstract. In the evolving landscape of education, integrating technology with pedagogical action research has become essential for fostering value orientation formation among learners. This study explores how digital tools and research-based reflective practices can enhance ethical, social, and professional values in education. By leveraging innovative technologies—such as artificial intelligence, digital learning platforms, and virtual collaboration—educators can create immersive and interactive learning environments that promote critical thinking and self-reflection. Pedagogical action research serves as a framework for continuous improvement, allowing educators to assess, adapt, and refine strategies for value-oriented teaching. The synergy between technology and research not only enhances the effectiveness of value formation but also contributes to the sustainability of educational innovations. This paper examines theoretical perspectives, practical methodologies, and case studies that illustrate the transformative potential of bridging technology with pedagogical action research in developing a value-driven educational framework.